Effect of human insulin and insulin analogue on some inflammatory markers and total antioxidant capacity in a sample of Iraqi type 1 diabetic children and adolescents - Noor Wafaa Hashim; Kadhim Ali Kadhim; Abbas Mahdi Rahmah (College of Pharmacy / Mustansiriyah University, 2022)
Background: Both human insulin and insulin analogue used in the treatment of type 1 diabetes mellitus. The modification in amino acids sequences of human insulin lead to produce analogue form which have a pharmacokinetic and pharmacodynamics effect near to normal human endogenous   insulin release. Aim of study: This study designed to compare between the effect of each type of insulin on high sensitive C-reactive protein and interleukin-6 and total antioxidant capacity in a sample of Iraqi type 1 diabetic children and adolescents. Study design: The study was enrolled on fifty-one Iraqi type 1 diabetic children and adolecence age range (6-18) year. The patients allocated into two groups, Group (1) includes 20 patients assigned to receive conventional human insulin (regular and NPH), and Group (2) includes 20 patients assigned to receive insulin analogue (insulin aspart and glargine) for three months. The inflammatory and antioxidant markers measured at baseline and after three months of intervention. Results: After three months of treatment, both insulin groups did not affect high sensetive C_reactive protein (hs-CRP) significantly from baseline to 3 months. Only insulin analogue reduced Interleukin-6 (IL-6) significantly, while human insulin reduced   level of IL-6 but it was not statistically significant. Both therapies reduced total antioxidant capacity (TAOC) significantly; however, insulin analogue had higher reduction percentage (15.1% vs. 5.7%) compared to the conventional insulin. Conclusion: Only insulin analogue reduced IL-6 significantly. Both types of insulins did not effect on hs-CRP. Both therapies reduce TAOC significantly.